Inhibiting Factors Analysis for the Implementation of the Go-Online Micro, Small and Medium Enterprises (MSME) - M N A Syahrin; E Susilawati (Peneliti.net, 2020)
The purpose of this study is to analyze the inhibiting factors for the implementation of the Go-Online Micro, Small and Medium Enterprises (MSME) program, which was initiated by the Ministry of Cooperatives and SMEs with the Indonesian Ministry of Communication and Information to provide marketing facilities for online MSME products. This research used a qualitative method with a descriptive approach using secondary data by utilizing literature studies in the form of research journals, regulations, or articles relating to this research. The results of this study indicate that two factors inhibit the implementation of the Go-Online MSME program caused by human factors and program socialization. The conclusion is that the human factor is caused by the lack of community skills for using internet access, while the Go-Online MSME program's socialization strategy factor is not appropriate in conducting this socialization program, therefore, the socialization of this program needs to be improved in the anticipatory socialization and encounter stage with a more informal approach to providing material for the public. Besides, the acquisition stage of the MSME Hub needs to be improved online and offline. Moreover, the participants' classification of this program needs to be classified based on education, age, and business management experience so that there is no gap between the material provided by the organizer and the ability of participants